Peran Pembina Asrama dalam Mengembangkan Motivasi Siswa Asrama Putera MA Sumatera Thawalib Parabek - Yulistia, Duwik; Elviana, Elviana; Hafizah, Hafizah (ANWARUL, 2024)
The dormitory builder is to be a parent, to be an educator, to be a murobby. Never worry about yourself because Allah Almighty will help anyone who helps his religion. Entrusting children in school The cottage is required to live in a dormitory. The formation of character that is considered more optimal is the reason for them to make boarding school a second home for their children. The role of dormitory coaches in developing the motivation for boarding students to excel is to understand the character of dormitory students, understand the situation and conditions, get closer, instill moral and moral values, instill responsible character, instill discipline values, describe challenges, instill the value of loving learning, give rewards, give provide guidance, provide support, provide containers, manage schedules, coordinate with other teachers, coordinate with parents, provide attention, boarding students.Familiarize positive things, train the ability of boarding students, give orders to boarding students, give advice, provide solutions, inspire, and generate student confidence. Achievement motivation, and other schools/readers, can make new theories in this study, as reference material to improve the role of coaches/educators in developing student achievement motivation. The aim of this research is to find out the role of dormitory supervisors in encouraging student motivation in helping to improve learning achievement in the dormitory. This research uses interview and observation methods. The results that the author can conclude are that the role of the supervisor is very influential in encouraging students to improve their learning achievement in the dormitory because the dormitory supervisor is the second parent after parents. The dormitory supervisor plays a very important role in encouraging participants to study.